Improving the Spectral Bandwidth of Superconducting Nanowire Single-Photon Detectors (SNSPDs) - Charaev, Ilya (Karlsruher Schriftenreihe zur Supraleitung / Hrsg. Prof. Dr.-Ing. M. Noe, Prof. Dr. rer. nat. M. Siegel, 2018)
This work presents a comprehensive investigation of the influence of geometry-dependent factors on performance metrics of superconducting single-photon detectors. With fundamental knowledge, main investigations are focused to extend the spectral bandwidth and to enhance the detection efficiency, especially in infrared range. The developed technology of single-spiral detectors and unconventional electron-beam lithography allows to improve the performance of superconducting detectors.